Financial Analysis Of Entrepreneurship Education - Etty Sri Wahyuni; Henry Aspan; Putri Mauliza (International Journal of Economics and Management Research, 2023)
This is a literature review on the study of the financial aspects of entrepreneurial activities. This study seeks to serve as a preliminary mapping in the process of developing learning materials and preparing financial competencies that entrepreneurs and aspiring entrepreneurs must master for business management. Collecting and analyzing literature on financial studies in order to construct a curriculum for financial education in the context of entrepreneurship is the method employed. This study's findings indicate that it is necessary to map learning materials and compile a study of a set of financial knowledge that enhances the business development skills of entrepreneurs. At the conclusion of this research, suggestions, and implications for future academic studies and learning are also provided.